Economic model predictive control for energy management of a microgrid connected to the main electrical grid. (September 2022) - Alarcón, Martín A.; Alarcón, Rodrigo G.; González, Alejandro H.; Ferramosca, Antonio
Abstract: Electric microgrids have become an interesting tool to facilitate the inclusion of renewable energies. Its architecture and control system plays a fundamental role in the implementation of these systems. This paper proposes a control strategy for the management of energy resources in a residential microgrid. The system is made up of a set of solar panels as renewable resource, a storage system formed by a lithium-ion battery bank and a consumption profile according to a residence. The microgrid will be connected to the main electrical grid and the proposed management strategy consists in the implementation of a suitable Economic Model Predictive Control, where it considers the costs of use for the different components of the microgrid, thus contemplating the participation of the system as an active agent in the electricity market. Simulations were carried out with different scenarios of available resources and prediction times. In all cases, the objectives fulfilling by satisfying the restrictions operational and technical imposed on the system. Highlights: Modelling of a residential microgrid. Participation in the electrical market of microgrids. Economic Model Predictive Control as a Energy Management System in microgrids.